A pyrene-involved luminescent MOF for monitoring 1-hydroxypyrene, a biomarker for human intoxication of PAH carcinogens. Issue 15 (3rd July 2018) - Zhou, You; Yang, Qian; Cuan, Jing; Wang, Yanan; Gan, Ning; Cao, Yuting; Li, Tianhua
Abstract : A robust pyrene-involved MOF is developed as a luminescent platform for sensitive detection of 1-hydroxypyrene, a human intoxication biomarker of PAH carcinogens, by utilizing the efficient host–guest π–π charge transfer interactions. Abstract : 1-Hydroxypyrene (1-HP) is a urinary metabolite of polycyclic aromatic hydrocarbons (PAHs), and can function as a convenient biomarker for human intoxication of PAH carcinogens. The development of simple 1-HP sensors with high sensitivity and fast response is highly desirable. Herein, we demonstrate that a robust microcrystalline MOF with fluorescent pyrene cores, NU-1000, exhibits sensitive luminescence detection of urinary 1-HP. The pyrene core within NU-1000 behaves as the signal converter, whose luminescence is significantly quenched upon coming into contact with 1-HP owing to the efficient π–π charge transfer interactions between highly conjugated 1-HP and pyrene cores in NU-1000. The pore confinement effect of the molecular-sized channel of NU-1000 facilitates the preconcentration of 1-HP within NU-1000, which makes 1-HP contact with NU-1000 more sufficient therefore enhancing the detection efficiency. The charge transfer-related quenching mechanism is elucidated by diffuse-reflectance UV-vis and electron paramagnetic resonance (EPR) measurements, and a radical pair state is observed in NU-1000 upon accommodation of 1-HP. This work provides important insights into the development of MOF-based luminescent sensors for 1-HP, and should stimulate further studies toward designing more efficient MOFs with highly conjugated luminescent cores for 1-HP sensing.